How Is Corporate Social Responsibility Important For The Financial Performance of Eurozone Firms? - Gonçalo Moura LESTRE; Mara Teresa da Silva MADALENO (Communications of International Proceedings, 2023)
Corporate Social Responsibility (CSR) seeks to optimize the benefit to an enterprise’s shareholders and stakeholders while intending to prevent or dampen the potential adverse effects of its activities. Considering that CSR covers a broad spectrum of issues, the concerned consumer will be, nowadays, aware of the need to demand from firms a responsible supply of products, but firms weigh the pros and cons aware of the profit-rational they usually follow. The main goal of this study is to understand if the practices of CSR have an impact on a firm's Financial Performance (FP), considering that few studies make an analysis covering different industrial sectors or companies from different countries. Different panel data methodologies were applied to data from 195 companies located in the Eurozone, during 2010-2019. The results confirm the initial suspicions, suggesting that CSR must be pursued in the process of strategic decision-making by the companies.
Keywords: Corporate Social Responsibility; Financial Performance; Panel Data; Euro Zone.